Predictors of international ski federation distance cross-country ranking - DuVall, A. J.; Moore, S. R.; Jensen, R. L. (ISBS Proceedings Archive (Michigan), 2019)
The Internationl Ski Federation (FIS) ranks Nordic skiers internationally based on race performance. This study aimed to determine if a relationship exists between FIS rankings and performance indicators such as maximum oxygen uptake, metabolic economy, and muscular endurance test performance. Muscular endurance (sit-up + pull-up and push-up + pull-up) were the best predictors utilizing stepwise regression resampling cross-validation (66 hold out groups). The sit-up + pull-up regression was a better fit than the push-up + pull-up (R2 = 0.506 & 0.349, p = 0.053 & 0.203, respectively). Muscular endurance test performance predicts FIS scores better than measures of oxygen consumption measures. Upper-body and core musculature may be an important determinant of performance, as it contributes to generation of propulsive forces in Nordic skiing.